Avaliação da segurança de torres metálicas para escoramentos de estruturas de concreto - Soeiro, Marcos Andrew Rabelo (2012)
It is well-known that most accidents with concrete structures occur in the construction phase, mainly due to stability failure of their shoring systems. These accidents can cause injuries, loss of life, significant construction delays, and finantial losses. Scaffolds are temporary structures that support construction loads, such as fresh concrete, steel, formwork and workers. First of all, finite element models composed of bars were created in order to study the structural behavior of steel scaffolds. Material and geometric nonlinear analyses were performed and the numerical results were compared with experimental results found in literature, showing good agreement. These analyses showed the importance of the boundary conditions and of the consideration of initial imperfections. Then, it was presented a methodology to verify the safety of steel scaffolding systems used in the construction of high-clearance concrete structures. The NBR 15696:2009 and BS 5975:2008 standards were adopted for the determination of external loads and initial imperfections. The internal forces were obtained from geometric nonlinear analyses. These forces were used to verify the safety of the steel members according to NBR 8800:2008. Three-dimensional and two-dimensional structural models (i.e. space and plane frames) were adopted. The results showed that, in some cases, it is possible to use plane models to analyze the scaffolding system, but, in other cases, it is necessary to use three-dimensional models. It was also noted that the scaffoldings failure occurs, in general, under combined compression and bending of the steel bars and also that the shear forces are not critical to the failure of these structures.